Late Antique decorative pins of the stylus type in Slovenia - Čaval, Saša (Arheološki vestnik, 2013)
The article presents a detailed typology and chronology of the Late Antique decorative pins of the stylus type found in Slovenia. This pin type derives from Roman toilet implements. The pins can be divided into five types with variants and appear across central and south-eastern Europe with a concentration in south-eastern Hungary, Slovenia and northern Italy. They were broadly in use from the end of the fourth to the beginning of the seventh century, though the majority dates to the sixth century